Epistemologi Pendidikan Islam Perspektif Fethullah Gülen dan Implementasinya terhadap Pendidikan Islam Integratif - Muhamad Restu Fauzi; Tasman Hamami (UIN Sunan Ampel Surabaya, 2022)
This research is motivated by education in most Muslim countries which are still lagging behind and there is still a dichotomy between Islamic education and secular education. As a result, the Muslim generation has obstacles in contributing to the development of world civilization, which should reflect the Islamic principles of rahmatan lil 'alamin. This is because Islamic education does not adjust to the progress and competition of the times. The epistemological thought of education by Fethullah Gülen tries to provide a solution to this problem by trying to abolish the dichotomy in education by creating an integrated Islamic education system. The purpose of this study is to find out in depth the epistemology of Islamic education from the perspective of Fethullah Gülen and its implementation of integrated Islamic education. The results of this study are: 1) The essence of the epistemology of Gülen's Islamic education is hikma, i.e. being able to combine useful knowledge accompanied by its practice in life; 2) The source of the epistemology of Islamic education comes from the senses, reason and true reports (news) that come from other people or Allah's messengers; 3) The purpose of Islamic education is to create insan kamil who are able to master religious, social and scientific knowledge and practice them in life in order to create a world full of peace and global progress; 4) The integrated Islamic education model according to Fethullah Gülen is similar to the neo-modernism integration model, that is integrating Islamic tradition with the modernity of civilization.